2006
DOI: 10.1097/01.hjh.0000217852.89745.dc
|View full text |Cite
|
Sign up to set email alerts
|

The 460Trp allele of α-adducin increases carotid intima–media thickness in young adult males

Abstract: The 460Trp allele of ADD1 contributes substantially to increase carotid IMT, in a male hormonal milieu only, at least in the young age range.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…12 In brief, we recruited YMs without previously diagnosed cardiovascular diseases. Family history of hypertension, smoking habits, and physical activity were carefully evaluated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…12 In brief, we recruited YMs without previously diagnosed cardiovascular diseases. Family history of hypertension, smoking habits, and physical activity were carefully evaluated.…”
Section: Methodsmentioning
confidence: 99%
“…In this context, lean YM carriers of the 129T allele might have higher EC levels and lower BP, whereas OH patients might have a further EC overactivity with unclear effects on BP. 6 This study aimed at investigating whether the FAAH P129T gene variant is associated with cardiovascular effects in YM participants of the Ancona Heart Doctor Study (AHDS) 12 and in an older population of male OH patients. To further study the possible effect of 129T FAAH variant in YMs, we also analyzed clinical parameters of a subset of YMs who underwent 9 years of follow-up.…”
Section: Faah Functional Variant and Bp In Young Malesmentioning
confidence: 99%
“…3 However, the 460Trp allele contributed substantially to the increased carotid intima media thickness in young, adult males. 4 In a study by Balkenstein et al, 5,6 a relationship was observed between the intima media thickness of the large muscular femoral artery and the ACE gene. This relationship is only seen in the presence of the a-adducin 460Trp allele, thus suggesting the presence of an epistatic interaction.…”
Section: Introductionmentioning
confidence: 97%
“…16 This genotyping of healthy subjects was performed in order to exclude the hypothesis that some variants might be present and/or more frequent specifically in patients with kidney cancer.…”
Section: Genotypingmentioning
confidence: 99%